La ceramica da cucina africana dalla cisterna romana di Spoletino (Civitella d’Agliano - VT) - Elefante, Mara (Rei Cretariae Romanae Fautorum Acta, 2024)
African cooking ware is a well-known unique case of utilitarian ware exported on large scale during Roman and Late Roman times. In the fill of the Roman cistern of Spoletino (Civitella d'Agliano - VT) this class is represented by 715 fragments that, considering the significant variety of cooking ware produced in the Tiber Valley in this period, are clear evidence of the great popularity of this kind of cooking ware. The first goal of this contribution is a complete typological study of this class, that in the inland sites is not always well represented as in Spoletino, where is significant and composed of all the usual different forms (lids, casseroles and pans), often in good condition and well preserved. The second goal, not less important, is to realise if the occurrence of the African cooking ware is caused just by its prestige or by a change in the cooking habits, fact understandable comparing the forms of the local cooking ware in this period, analysing if there are local imitations of the African forms and considering the local trade.